Optical Coherence Tomography Guided Intravascular Lithotripsy in the Peripheral Vasculature: Technique and Case Series Analysis - Rohit Mehra; Vikram Patra; Rishi Dhillan; Rahul Merkhed; C V N M Dattatraya (Indian Journal of Vascular and Endovascular Surgery)
Objectives: Luminal calcification of human vasculature has been one of the most dreaded and concerning issues with prognosis-defining ramifications. The calcium-disrupting potential exhibited by intravascular lithotripsy (IVL) technology has seen a limited deployment in peripheral vasculature. This study was an endeavor to utilize optical coherence tomography (OCT) as a therapeutic imaging modality in in vivo human arterial vasculature, in amalgamation with IVL for producing realistic intraoperative evidence of calcium fragmentation and luminal expansion, stent bed preparation, and ascertain utility without the usage of contrast. Patients and Methods: A prospective, observational, two-center study case series analysis, which enrolled 24 patients with peripheral arterial disease requiring the usage of IVL. The single-operator exchange OCT fiber pullback was utilized to ascertain arterial calcium load, depth of calcium, and lesion characters to minimize therapeutic misses. The same 0.014” wire-based platform was used to deploy commercially available IVL balloons of appropriate profile. The IVL balloon was sized 1.1:1 with the target artery diameter. The guidance from OCT pullback was used to concentrate lithotripsy energy at the calcium-laden areas of the target artery. Intravascular ultrasound was used to obtain grayscale comparable intraoperative images in a few cases. The primary endpoints were procedural success as defined by residual stenosis ≤30% without flow-limiting dissection, symptomatic relief, and healing of preexisting limb ulcers. The secondary endpoints were any major adverse limb events, including arterial perforation, abrupt vessel closure, no-reflow, and all-cause mortality at 6 months. The study was approved by an institutional ethical committee, and standard statistical tools were used to do the descriptive analysis. Results: The mean age of the participants was 64 (5) years, with a male gender predilection (83.3% males). The comorbidities present in the cohort were diabetes mellitus II, coronary artery disease, dyslipidemia, and hypertension were observed in 21 (87.5%), 20 (83.3%), 17 (70.8%), and 14 (58.3%) patients, respectively. A total of 19 (79.1%) of the patients had presented with a nonhealing ulcer in the target limb. A total of 12 (50%) patients were current smokers and 6 (25%) were reformed smokers. Renal compromise in the form of deranged renal parameters or established renal disease was observed in 13 (54.2%) patients. The average target vessel diameter was 4.6 (2.1) mm, and the maximum and minimum stenosis observed with OCT before IVL was 91% and 46%, respectively. Stenosis at multiple levels was observed in 11 (45.8%) patients. The calcium arch in the target vessel on OCT was found to be <1800, 1800–2700, and 3600 in 10 (41.7%), 5 (20.8%), and 9 (37.5%) patients, respectively. The average contrast volume used was 9.5 ml. Post-IVL stents were used in 3 (12.5%) patients, in whom a >30% residual stenosis or lesion recoil was found. The minimal luminal area increase observed in iliac arteries, superficial femoral arteries, and infragenicular arteries was at an average of 8 sq mm, 6.8 sq mm, and 3.4 sq mm, respectively. Conclusion: The ability of OCT to delineate medial calcium, calcium nodules, along with an unparalleled edge of a transmural optical biopsy acts as a force-multiplier in strategically targeting IVL to obtain maximal outcome. Synergistically, the two techniques seem to have path-breaking capabilities.